Jewish Occupational Selection : Education, Restrictions, or Minorities? - Maristella Botticini; Zvi Eckstein (Institute for the Study of Labor (IZA), 2004)
This paper documents the major features of Jewish economic history in the first millennium to explain the distinctive occupational selection of the Jewish people into urban, skilled occupations. We show that many Jews entered urban occupations in the eighth-ninth centuries in the Muslim Empire when there were no restrictions on their economic activities, most of them were farmers, and they were a minority in all locations. Therefore, arguments based on restrictions or minority status cannot explain the occupational transition of the Jews at that time. Our thesis is that the occupational selection of the Jews was the outcome of the widespread literacy prompted by a religious and educational reform in the first century ce, which was implemented in the third to the eighth century. We present detailed information on the implementation of this religious and educational reform in Judaism based on the Talmud, archeological evidence on synagogues, the Cairo Geniza documents, and the Responsa literature. We also provide evidence of the economic returns to Jewish religious literacy.
Keywords: O10; J10; N30; J20; 330; first millennium; human capital; Jewish economic history; migration; occupational choice; religion and social norms; Wirtschaftsgeschichte; Sozialgeschichte; Humankapital; Urbanisierung; Mobilität; Soziale Mobilität; Juden